Producing the Graduate Student: A Textual Analysis of Funding Through Scholarship Application - Thomas-Long, Roslyn (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
This paper originated from the fierce debate on graduate student funding that arose at the University of Toronto in 2000. As a graduate student at the time, I was very interested in the social processes of becoming a graduate student in Canadian universities. Using a textual analysis of graduate students' scholarship applications, the paper examines the ways in which the funding process sorts graduate students into worthwhile recipients; in effect, replicating the processes that produce a business-as-usual ethos in funding practices.